Clinical Guide to Helping New Parents: The Couple CARE for Parents Program - Halford, W. Kim (Springer, 2015)
This accessible guide details an evidence-based educational program to help couples adapt to parenthood while minimizing the inevitable stress on the relationship. Complete with content, rationales, activities, and client materials, its flexible format allows for home and office visits and phone/online support across the transition, starting during pregnancy and continuing into early infancy. Activities build on themes of caring, change, and cooperation as couples learn to identify and address sources of conflict, solve infant-care problems, and to become optimal partners as well as optimal parents. The book's hands-on presentation includes chapter highlights, boxed "Practice Tips" and "Clinical Connections" sections, client handouts and worksheets, and examples of clinician interactions with couples.